Functional modulation of nuclear steroid receptors by tauroursodeoxycholic acid reduces amyloid beta-peptide-induced apoptosis - Sola, Susana (2015)
Tauroursodeoxycholic acid ( TUDCA) prevents amyloid beta-peptide (A beta)-induced neuronal apoptosis, by modulating both classical mitochondrial pathways and specific upstream targets. In addition, activation of nuclear steroid receptors (NSRs), such as t